2005
DOI: 10.1007/s00239-004-0340-0
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intralocus Recombination Drive MHC Class IIB Gene Diversification in a Teleost, the Three-Spined Stickleback Gasterosteus aculeatus

Abstract: The mutational mechanism underlying the striking diversity in MHC (major histocompatibility complex) genes in vertebrates is still controversial. In order to evaluate the role of inter- and intragenic recombination in MHC gene diversification, we examined patterns of nucleotide polymorphism across an exon/intron boundary in a sample of 31 MHC class IIB sequences of three-spined stickleback (Gasterosteus aculeatus). MHC class IIB genes of G. aculeatus were previously shown to be under diversifying (positive) se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
100
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 56 publications
7
100
1
Order By: Relevance
“…The scarce available information suggests that both types of recombination may occur at a similar rate within class II B (Reusch and Langefors, 2005). In addition, high similarity among sequences derived from different MHC loci (apparent paralogs) suggests that inter-locus gene conversion may be an important evolutionary mechanism in fish (Reusch and Langefors, 2005;Aguilar and Garza, 2007) and birds (Edwards et al, 1995;Wittzell et al, 1999a, b;Burri et al, 2008). In grouse, we found that ca.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…The scarce available information suggests that both types of recombination may occur at a similar rate within class II B (Reusch and Langefors, 2005). In addition, high similarity among sequences derived from different MHC loci (apparent paralogs) suggests that inter-locus gene conversion may be an important evolutionary mechanism in fish (Reusch and Langefors, 2005;Aguilar and Garza, 2007) and birds (Edwards et al, 1995;Wittzell et al, 1999a, b;Burri et al, 2008). In grouse, we found that ca.…”
Section: Discussionmentioning
confidence: 56%
“…Although the evidence for inter-locus recombination at MHC is now wellestablished in different vertebrate taxa (Hughes and Nei, 1989;Cardenas et al, 2005;Zagalska-Neubauer et al, 2010), including galliforms (Strand et al, 2013), the relative rates of inter-and intralocus gene conversion at MHC are difficult to assess. The scarce available information suggests that both types of recombination may occur at a similar rate within class II B (Reusch and Langefors, 2005). In addition, high similarity among sequences derived from different MHC loci (apparent paralogs) suggests that inter-locus gene conversion may be an important evolutionary mechanism in fish (Reusch and Langefors, 2005;Aguilar and Garza, 2007) and birds (Edwards et al, 1995;Wittzell et al, 1999a, b;Burri et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, pathogen-driven balancing selection (through overdominance, negative frequency dependence or temporal/spatial heterogeneity in pathogen phenotype) is thought by many to be the main force driving MHC evolution (Klein and O'Huigin, 1994;Parham and Ohta, 1996;Edwards and Hedrick, 1998;Hedrick and Kim, 2000;Jeffery and Bangham, 2000). Evidence of selection on MHC genes has traditionally come from four sources (Hughes and Yeager, 1998): (a) long persistence times for MHC alleles compared with neutral expectation (often resulting in trans-specific polymorphism) (Figueroa et al, 1988;Lawlor et al, 1988;McConnell et al, 1988;Klein et al, 2007); (b) frequency distributions of MHC alleles in natural populations that are more even than that expected under a neutral model (Hedrick and Thompson, 1983;Markow et al, 1993); (c) high levels of nonsynonymous versus synonymous substitutions in codons for peptide binding residues (Hughes and Nei, 1988, 1989; and (d) homogenization of introns with concurrent diversification of exons at MHC loci (Cereb et al, 1997;Reusch and Langefors, 2005).…”
Section: Introductionmentioning
confidence: 99%